Deformation dynamics of the solid structural unit from an external action - A.A. Mochalov; A.A. Gaisha; K.D. Evfimko (Журнал нано- та електронної фізики)
In this work we present the model for study the solid deformation dynamics based on the structural unit method. The solution results of some model equations are given. Time dependence of the sections relative displacement of a structural unit during the uniaxial longitudinal deformation is graphically represented.